2019
DOI: 10.5194/essd-2019-145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

1-km monthly temperature and precipitation dataset for China from 1901–2017

Abstract: High-spatial-resolution and long-term climate data are highly desirable for understanding climate-related natural processes. China covers a large area with a low density of weather stations in some regions, especially in mountainous regions. 10This study describes a 0.5' (~1 km) dataset of monthly air temperatures at 2 m (minimum, maximum, and mean TMPs) and precipitation (PRE) for China from 1901-2017. The dataset was spatially downscaled from 30' climatic research unit (CRU) time series dataset with the clim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(105 citation statements)
references
References 0 publications
2
103
0
Order By: Relevance
“…The elevation and slope were calculated from SRTM DEM with a spatial resolution of 90 m downloaded from the USGS website. The raster-based precipitation and temperature data from 1986 to 2015 were collected from the 1 km monthly temperature and precipitation dataset 38 (available at https://doi.org/10.5281/zenodo.3114194 for precipitation and https://doi.org/10.5281/zenodo.3185722 for air temperatures), which were created by spatially downscaling with the resolution of 0.5 arcminutes (~ 1 km). The socio-economic data including population, income, grain yield, and labor for each administration region were obtained from local statistic yearbook 1985–2015 (each yearbook every five years) (Gansu bureau of statistics).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…The elevation and slope were calculated from SRTM DEM with a spatial resolution of 90 m downloaded from the USGS website. The raster-based precipitation and temperature data from 1986 to 2015 were collected from the 1 km monthly temperature and precipitation dataset 38 (available at https://doi.org/10.5281/zenodo.3114194 for precipitation and https://doi.org/10.5281/zenodo.3185722 for air temperatures), which were created by spatially downscaling with the resolution of 0.5 arcminutes (~ 1 km). The socio-economic data including population, income, grain yield, and labor for each administration region were obtained from local statistic yearbook 1985–2015 (each yearbook every five years) (Gansu bureau of statistics).…”
Section: Study Area and Methodsmentioning
confidence: 99%
“…Finally, given that sampling was conducted across 2 years, year was included as random factor. We considered including climatic variables—average annual temperature and precipitation from 2011 to 2015 as explanatory variables, which were obtained from Loess plateau science data center, National Earth System Science Data Sharing Infrastructure, National Science & Technology Infrastructure of China (http://loess.geodata.cn) (Peng et al., 2019). However, we finally excluded these climatic variables due to their high correlation with latitude and longitude (Table A2).…”
Section: Methodsmentioning
confidence: 99%
“…Not only can we make full use of the time-series weather stations, but also consider the satellites-driven anomaly as either independent spline variables or linear covariates to further improve the accuracy of the final monthly climate surface. Our results showed that ChinaClim_timeseries was indeed a better climate dataset than Peng's climate surface and CHELSAcruts in China with higher R 2 , and lower RMSE and MAE, especially in high cold https://doi.org/10.5194/essd-2020-361 Previous studies indicated that baseline climatology surface, considering detailed topographic information, the effects of distance to the nearest coast and satellite-driven variables, is physically representative and has a fine-scale distribution of meteorological variables (Marchi et al, 2019;Mosier et al, 2014;Peng et al, 2017;Platts et al, 2015). Thus, a superior baseline climatology surface is helpful to improve the accuracy of the long-term monthly climate surface.…”
Section: Discussionmentioning
confidence: 99%
“…There was a large amount of evidence to suggested that the CAI method can better generate longterm monthly climate surface (Abatzoglou et al, 2018;Becker et al, 2013;C. Vega et al, 2017;Karger et al, 2017;Mosier et al, 2014;Peng et al, 2019;Willmott and Robeson, 2010). Our results proved Peng's climate surface and CHELSAcruts datasets, relying on coarse CRU anomaly and high-quality baseline climatology surfaces with CAI method, had relatively high accuracy (high R 2 ) with a few weather stations in China at 1km spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation